In Type 2 Diabetes Mellitus, normalization of hemoglobin A1c accompanies reduced sensitivity to pressure at the sternum - Faber, Jens; Ballegaard, Søren; Ørsted, Nanna; Eldrup, Ebbe; Karpatschof, Benny; Gyntelberg, Finn; Hecquet, Sofie Korsgaard; Gjedde, Albert (Frontiers in Neuroscience, 2023)
Background The autonomic nervous system (ANS) maintains glucose homeostasis. While higher than normal glucose levels stimulate the ANS toward reduction, previous findings suggest an association between sensitivity to, or pain from, pressure at the chest bone (pressure or pain sensitivity, PPS) and activity of the ANS. A recent randomized controlled trial (RCT) of type 2 diabetes (T2DM) suggested that addition of an experimental, non-pharmacological intervention more effectively than conventional treatment lowered the levels of both PPS and HbA1c. Materials and analyses We tested the null hypothesis that conventional treatment (n = 60) would reveal no association between baseline HbA1c and normalization of HbA1c in 6 months, related to change of PPS. We compared the changes of HbA1c in PPS reverters who experienced a minimum reduction of 15 units of PPS and in PPS non-reverters who experienced no reduction. Depending on the result, we tested the association in a second group of participants with addition of the experimental program (n = 52). Results In the conventional group, PPS reverters experienced normalization of HbA1c that corrected the basal increase, thus disproving the null hypothesis. With the addition of the experimental program, PPS reverters experienced similar reduction. The reduction of HbA1c among reverters averaged 0.62 mmol/mol per mmol/mol increase of baseline HbA1c (P < 0.0001 compared to non-reverters). For baseline HbA1c ≥ 64 mmol/mol, reverters averaged 22% reduction of HbA1c (P < 0.01). Conclusion In consecutive analyses of two different populations of individuals with T2DM, we demonstrated that the higher the baseline HbA1c, the greater the reduction of HbA1c but only in individuals with a concomitant reduction of sensitivity to PPS, suggesting a homeostatic effect of the autonomic nervous system on glucose metabolism. As such, ANS function, measured as PPS, is an objective measure of HbA1c homeostasis. This observation may be of great clinical importance.